Analisis Kualitas Layanan Website LMS STMIK Bandung Terhadap Kepuasaan Pengguna Menggunakan Metode Webqual 4.0 dan Importance Performance Analysis (IPA) - Versanika, Dayanni Vera; Salsabila, Nadiva (Jurnal Bangkit Indonesia, 2025)
In the digital era, technological innovation plays a significant role in the development of various sectors, including education. This study aims to measure the level of user satisfaction among students and to identify the dimensions of Webqual 4.0 and Importance Performance Analysis (IPA) that influence the quality of the Learning Management System (LMS) website at STMIK Bandung. The methodology employed includes Webqual 4.0 and Importance Performance Analysis (IPA). A quantitative approach using questionnaires was applied to students who utilize the website. Data was collected through questionnaires with variables of usability, information quality, and service interaction quality, comprising 22 indicators. Importance Performance Analysis (IPA) was used to identify indicators that require improvement or maintenance based on user performance and expectations. The results of this study reveal an average gap of 0 between the expectations and performance of the LMS website at STMIK Bandung, indicating that the service quality meets expectations. Nevertheless, certain indicators such as USB1 and USB2 exceed user expectations. The hypothesis linking website quality to user satisfaction is accepted, particularly as the variables USB and SIQ demonstrate a significant correlation with user satisfaction. The Webqual Index (WQI) indicates that the website is categorized as good, with a score of 0.87 (87%). Through Importance-Performance Analysis, it is recommended to focus on USB8. The practical implications of this research provide an overview of the service quality of the LMS website at STMIK Bandung and can serve as a guideline for the university administration to enhance the quality of the existing academic platform.